2020
DOI: 10.3390/s20102826
|View full text |Cite
|
Sign up to set email alerts
|

IoT Wearable Sensors and Devices in Elderly Care: A Literature Review

Abstract: The increasing ageing global population is causing an upsurge in ailments related to old age, primarily dementia and Alzheimer’s disease, frailty, Parkinson’s, and cardiovascular disease, but also a general need for general eldercare as well as active and healthy ageing. In turn, there is a need for constant monitoring and assistance, intervention, and support, causing a considerable financial and human burden on individuals and their caregivers. Interconnected sensing technology, such as IoT wearables and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
138
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(143 citation statements)
references
References 44 publications
1
138
0
4
Order By: Relevance
“…He recognized that wearable sensors and actuators, coupled with information and communication technologies, might be useful in cost-effective remote healthcare services. The performed study results were comparable to the findings of Stavropoulos et al presented in the comprehensive, systematic review of studies in IoT wearables and devices for eldercare [ 13 ]. They identified four major health focus areas: Alzheimer’s disease, Parkinson’s disease, dementia, and fall detection.…”
Section: Related Work and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…He recognized that wearable sensors and actuators, coupled with information and communication technologies, might be useful in cost-effective remote healthcare services. The performed study results were comparable to the findings of Stavropoulos et al presented in the comprehensive, systematic review of studies in IoT wearables and devices for eldercare [ 13 ]. They identified four major health focus areas: Alzheimer’s disease, Parkinson’s disease, dementia, and fall detection.…”
Section: Related Work and Discussionsupporting
confidence: 88%
“…This knowledge is also particularly crucial for policymakers and manufacturers of medical devices as the input data for the design and development process and clinical evaluation of medical devices. The need for this novel knowledge has been highlighted in the conclusion of a recently published comprehensive—a systematic review by Stavropoulos et al [ 13 ]. The authors concluded that future work might focus on the aspect of IoT (Internet of things) for eldercare like human needs or hardware and software features.…”
Section: Introductionmentioning
confidence: 99%
“…Third, wearables can facilitate remote patient monitoring and provide proactive and faster data access to physicians, resulting in improved health outcomes [ 4 , 5 ] and reduced number of physician visits [ 6 ]. Fourth, these devices can be particularly useful for patients with chronic conditions [ 7 ], patients with cardiovascular risks [ 8 ], and elderly populations [ 9 ]. Therefore, the use of wearable devices has the potential to significantly improve health care delivery and reduce costs.…”
Section: Introductionmentioning
confidence: 99%
“…Making the most effective use of the expertise available, from technologists, clinicians, and participants alike, was our overriding priority and strength. We clearly were informed by principles from HCD (28) and of course by aspects of "design thinking" more broadly (33). But pragmatic adaptation of these techniques to fit our circumstances, maximize our strengths, address our weaknesses, and solve the problems we encountered, became more influential on the shape of our eventual process than an abstract model.…”
Section: Discussionmentioning
confidence: 99%
“…For RMTs, which inherently have some manifestation within participants' everyday lives, the need to understand participants' perspectives is especially important. In the Innovative Medicines Initiative 2 (IMI)-funded, "Remote Assessment of Disease and Relapse-Central Nervous System" (RADAR-CNS, https://www.radar-cns.org/), it is hypothesized that Human-centered Design (HCD) methods might be usefully adapted to the challenge of selecting RMTs, and a novel threestage iterative process based on HCD principles has been proposed (28).…”
Section: Patient and Public Involvementmentioning
confidence: 99%